Answer:
Step-by-step explanation:
A= πr²
A= 22/7 multiply by the radius.
Divide 9.4cm by 2.
Whatever you get is your answer. Now take the formula I have shown you above. Whatever you get is your answer.
Answer:
5b + 12c
Step-by-step explanation:
-5a +5 a = 0
12b-7b = 5b
12c= 12c
therefore you have the expression 5b+12c
<span>y=-4/x+1 is ambiguous, since it's not immediately clear whether you meant
-4
y = -4/x + 1 or y = ---------
x+1
I'm going to assume that the latter is what you meant.
1. Interchange x and y, obtaining:
-4
x = --------
y+1
2. Solve this for y, obtaining y+1 = -4/x, or xy + x = -4, or
-x - 4
xy = -x-4, or y = ---------
x
-1 -1 4
3. Replace y with f (x): f (x) = -1 - -----
x
This last result has the correct form.</span>
Answer:
yes they are
Step-by-step explanation:
Step-by-step explanation:
hey.....
how are uh